Efeitos da equação de estado em hidrodinâmica relativística através de alguns observáveis - Dudek, Danuce Marcele [UNESP] (2014)
We present results of a systematic study of the role of the equation of state in the hydrodynamic model. We simulate Au+Au collisions for two energies of the Relativistic Heavy Ion Collider (RHIC), 130 and 200 GeV per nucleon, in order to compare our results to the collider data. By using the same initial conditions and freeze-out scenario, we analysed the eﬀects of diﬀerent equations of state on some physical observables trough the results of their respective hydrodynamical evolution. The observables of interest investigate here are particle spectra, elliptic ﬂow, used to study the impact of the equations of state on ﬁnal state anisotropies, and radii parameters estimated by the Hambury-Brown-Twiss eﬀect (HBT). Three diﬀerent types of equation of state are studied, each focusing on diﬀerent features of the system, such as the nature of the phase transition, strangeness and baryon densities. These diﬀerent equations of state imply diﬀerent hydrodynamic responses on the observables. Although the three equations of state used in the calculations describe the data reasonably well, some small diﬀerences are observed, showing weak sensitivity of the results on the particular choice of equation of state